ANALISIS PENGARUH KOMPETENSI, INDEPENDENSI, DAN ETIK PADA KUALITAS AUDIT DI PERWAKILAN BADAN PENGAWASAN KEUANGAN PEMBANGUNAN - -, Murtapa; Budiarta, Ketut (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
The purpose of this penielitian is to analyze the effect of competence, independence and observance of the code of conduct with a quality audit at the Legislative Financial and Development Supervisory Agency (BPKP) of Bali. This research was conducted in BPKP Representative Office of Bali Province. Samples are taken as many as 61 officials Functional Auditor (PFA), with a probability sampling method on condition PFA which has certified auditor and is not on duty outside bali during sampling. Data collected through the questionnaire technique. The analysis technique used is multiple linear regression using SPSS. The analysis showed that there is positive and significant correlation between competence, independence and ethics on audit quality. it means increased competence and to uphold and safeguard the independence and adherence to a code of conduct to maintain the quality of audits produced by the Auditor Functional Officer (PFA).
Keywords: Competence, Independence, Ethics, Quality Audit